2018
DOI: 10.11118/actaun201866051227
|View full text |Cite
|
Sign up to set email alerts
|

Testing Wagner's Law and Keynesian Hypothesis in Selected Post-Soviet Countries

Abstract: The aim of this research is to test Wagner’s law and Keynesian hypothesis in 9 Post‑Soviet countries – Estonia, Latvia, Lithuania, Uzbekistan, Azerbaijan, Georgia, Kyrgyz Republic, Moldova, and Ukraine. For this purpose, long‑ and short‑run causality between real per capita GDP and real per capita government expenditures are estimated by employing ARDL modelling approach. Estimation results support validity of Wagner’s law for Latvia, Lithuania, Uzbekistan, Georgia, Kyrgyz Republic and Ukraine, and validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…This is because Wagner's law is valid for EU member transition economies for the 1995-2019 period. Moreover, the results arising from this research are supported in the literature by Thornton (1999), Kolluri et al (2000), Al-Faris (2002), Wu et al (2010), Paparas and Stoian (2016), Abbasov and Aliyev (2018), Ağayev (2012).…”
Section: Dumitrescu and Hurlin (2012) Panel Granger Causality Testsupporting
confidence: 81%
See 1 more Smart Citation
“…This is because Wagner's law is valid for EU member transition economies for the 1995-2019 period. Moreover, the results arising from this research are supported in the literature by Thornton (1999), Kolluri et al (2000), Al-Faris (2002), Wu et al (2010), Paparas and Stoian (2016), Abbasov and Aliyev (2018), Ağayev (2012).…”
Section: Dumitrescu and Hurlin (2012) Panel Granger Causality Testsupporting
confidence: 81%
“…Paparas and Stoian (2016) conducted a study on Romania and concluded that five versions of Wagner's law are valid. Abbasov and Aliyev (2018) studied nine former Soviet countries and concluded that Wagner's law is valid in Latvia, Lithuania, Uzbekistan, Georgia, Kyrgyzstan, and Ukraine, while Keynes's theory is valid in Estonia, Uzbekistan, Azerbaijan, Kyrgyzstan, and Moldova. Ağayev (2012) analyzed ten former Soviet countries and obtained results that support Wagner's law.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that a 1% increase in government capital expenditures is associated with a 0.45%, 0.38% and 0.39% increase in real non-oil GDP by VECM, FMOLS and DOLS estimates, respectively. Besides that, Abbasov and Aliyev (2018) between total GDP and government expenditures in Azerbaijan. Abbasov (2012Abbasov ( , 2013 estimated the dependence of income per capita on the state budget expenditure items.…”
Section: Source: Own Compilationmentioning
confidence: 99%
“…It should be noted that the ARDL method is more valuable than other cointegration approaches and offers reliable results for small samples (Abbasov and Aliyev, 2018).…”
Section: Ardlbtmentioning
confidence: 99%